SIMRS as a Public Policy Tool for Decision Making at Otanaha Hospital - Nelty U. Aliwu; Asna Aneta; Rusli Isa (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Digital transformation in the health sector requires regional hospitals to optimize the implementation of the Hospital Management Information System (SIMRS) as a public policy instrument that supports timely and evidence-based decision-making. This study analyzes the role of SIMRS at Otanaha Regional Hospital, Gorontalo City, by examining its contribution to managerial effectiveness, data quality, and health service governance. Using a descriptive-analytical approach, the research draws on observations, in-depth interviews, and a review of the hospital’s 2024–2025 performance documents. The findings indicate that SIMRS implementation remains suboptimal: 64% of service units still rely on manual records, 48% of administrative staff have not mastered key system features, and patient data updates are delayed by an average of 7.4 hours. Data completeness reaches only 82%, accompanied by a strong negative correlation (r = –0.71) between data delays and managerial decision-making speed. These results highlight the need to strengthen organizational capacity, establish structured digital governance, and cultivate a data-driven institutional culture to enhance SIMRS effectiveness as a public policy instrument.